UK in European Security: New Opportunities or a Path to Nowhere? - D. V. Shikhov (Vestnik MGIMO-Universiteta)
Despite Britain's traditionally ambivalent attitude towards deepening the European integration, in late 1990s - early 2000s London seemed to become a key driver of European defence and security cooperation. T.Blair and J.Chirac have set ambitious goals including the development of a European Rapid Reaction Force. However most targets have never been achieved due to concerns about undermining NATO's role and Britain's as well as other EU members' unwillingness to undertake real steps to strengthen defence and security cooperation. In late 2000s the prospects of defence integration within the EU were becoming more and more vague, and the D.Cameron coalition government opted for bilateral Franco-British cooperation. Today London remains among key opponents to the European defence but the paradox is that EU defence integration without Britain - which is along with France a leading EU military power-would be at least ineffective. With US activities gradually shifting from Europe to Asia-Pacific Britain may well take the lead in European security without any damage to Transatlantic Relations.